Should self-regulated learning be integrated with cognitive load theory? A commentary. (October 2017) - Sweller, John; Paas, Fred
Abstract: Research on either cognitive load theory or self-regulated learning usually proceeds without reference to the other theory. In this commentary, we have commented on the editorial introduction and the six papers included in this Special Issue intended to indicate possible links between the two theories. To assist in this process, we have analysed some of the characteristics of both theories that either facilitate or impede the establishment of links. We conclude that while links are possible, the many differences between the theories present considerable barriers that will need to be overcome. Highlights: Integrating cognitive load theory and self-regulated learning could be useful. There are differences between both the theories and their procedures. These differences will need to be addressed before integration.